A soluble form of Siglec-9 provides a resistance against Group B Streptococcus (GBS) infection in transgenic mice. (October 2016) - Saito, Mitsumasa; Yamamoto, Sayo; Ozaki, Kinuyo; Tomioka, Yukiko; Suyama, Haruka; Morimatsu, Masami; Nishijima, Ken-ichi; Yoshida, Shin-ichi; Ono, Etsuro
Abstract: Group B Streptococcus (GBS) is a leading cause of invasive bacterial infections in human newborns. A key GBS virulence factor is its capsular polysaccharide (CPS), possessing terminal sialic acid residues that suppress host immune response and provide a survival advantage to the pathogen. CPS binds to Siglec-9 expressed on neutrophils, which is expected to down-regulate the immune responsiveness of neutrophils. We hypothesized that a soluble form of Siglec-9 (sSiglec-9) competitively inhibits a binding of CPS to Siglec-9 on immune cells, leading to provide antibacterial benefit against GBS infection in the transgenic mouse line expressing sSiglec-9 (sSiglec-9 Tg). The sSiglec-9 in the sera of sSiglec-9 Tg bound to the sialylated-GBS strains belonging to serotypes Ia, Ib, II, III, IV and V in whole GBS cell ELISA. When GBS cells of serotype III that is a common serotype in late-onset GBS disease (LOD) were intraperitoneally inoculated into sSiglec-9 Tg, sSiglec-9 Tg showed a significant resistance as compared with non-transgenic littermates. Furthermore, GBS serotype III organisms were not detected in cultures of the blood from surviving mice (<1 × 10 3  CFU/ml). These results indicated that sSiglec-9 Tg mice were more efficient in eliminating GBS and survived better after the intraperitoneal challenge with GBS serotype III bacteria. Highlights: Transgenic mice expressing soluble Siglec-9 showed resistance against GBS. Soluble Siglec-9 bound to GBS strains from serotypes Ia, Ib, II, III, IV and V. Transgenic mice expressing soluble Siglec-9 eliminated GBS more efficiently. Soluble Siglec-9 had an antibacterial benefit against GBS serotype III infection.